Part of Speech Tagging untuk Bahasa Jawa dengan Hidden Markov Model - Ryan Armiditya Pratama; Arie Ardiyanti Suryani; Warih Maharani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2020)
Indonesia has many cultures and local language, one of the most is Javanese with the Javanese language. The Javanese language is used in the region of Central Java and East Java, the word structure of the Javanese language has a similar to the Indonesian word class. Part of Speech (POS) Tagging is a process for labeling word classes for each input word that corresponding. POS Tag for Indonesian Language has been done a lot and got very good accuracy with various method application. This study aims to provide the word class label for Javanese language and the datasets used was obtained from online news with Javanese Ngoko language. The method used in this study is the Hidden Markov Model (HMM) with use of the HMM method get the highest accuracy is 96.2 %. Keywords: POS Tagging, Javanese Ngoko, Labeling, Hidden Markov Model